The theory and practice of the Dewey decimal classification system - Satija, Mohinder Partap, 1949- (Chandos information professional series., 2007)
This book examines the history, management and technical aspects of the Dewey Decimal Classification system (DDC), the world's most popular library classification. The main emphasis is on explaining the structure and number building techniques in the DDC. The book reviews all aspects of subject analysis and number building by the latest edition of the DDC.